DIABETIC FOOT: SELF-CARE AND RISK OF COMPLICATIONS IN TYPE II DIABETIC PATIENTS (Fiep Bulletin - online, 2013)
BACKGROUND: Adherence to Diabetes Mellitus (DM) treatment (pharmacological and non-pharmacological) is of great importance to reducing the incidence of complications. OBJECTIVES: To identify the level of self-care in patients with type II DM and assess their level of feet complications risk. METHODS: This cross-sectional study included type II diabetics, aged over 18 years with preserved cognition, not hospitalized, forming a convenience sample. The rate of self-care was assessed by the Self-Care Activities Questionnaire with Diabetes (QAD). The level of risk for complications was evaluated by inspection of feet and palpation (distal pulses, superficial and deep sensitivity). RESULTS: The sample consisted of 42 individuals, 67% women, mean age 63 ± 11 years, who were diagnosed for 131 ± 91 months, that use oral medications for 123 ± 87 months (100% of the sample) and insulin for 27 ± 46 months (43% of the sample). In QAD, greater adherence was observed "take the indicated number of diabetes pills" aspect (6.9 ± 0.7 days per week) and lowest in "conduct specific physical activities" aspect (2.0 ± 2.6 days per week). Regarding the risk of complication in feet, 35 patients had low risk (no neuropathy = 83% of sample), 1 patient had moderate risk (neuropathy and no other abnormalities = 2% sample) and 6 patients were high risk patients (15%). CONCLUSION: It was concluded that most diabetic patients tested showed low risk of developing feet complications, with low prevalence of neuropathy, ulcers and amputations. It has been shown that the level of adherence to self-care is high in relation to the use of medications and is low in relation to the practice of physical activities.
Keywords: Diabetic foot; Self-Care; Risk of complications